0
$\begingroup$

On the table, there are two coins, with head probability each $p_1=\frac{1}{5}$ and $p_2=\frac{1}{7}$.

I choose at random one of the two coins and repeatedly launch it. I get the first head on the 4th launch. What is the probability that I have in my hand the coin for which $p_1=\frac{1}{5}$ ?

I have thought that if I have launched the first coins, to get head at the 4th throw, the probability is $0{,}5\cdot (\frac{1}{5})^4$ because we have probability of $0{,}5$ for the chosen of the coins and every throw of the coins is independent of the others and have probability $\frac{1}{5}$

But I don't think this is the right solution

$\endgroup$
5
  • 4
    $\begingroup$ The probability that you choose the first coin and get the first head on the $4$th launch is $0.5 \times (\frac45)^3\times \frac15$. Similarly the probability that you choose the second coin and get the first head on the $4$th launch is $0.5 \times (\frac67)^3\times \frac17$. You need to combine these results to get the answer $\endgroup$
    – Henry
    Mar 30 '17 at 6:18
  • $\begingroup$ Unfortunatly I can't understand the answer... And I can't figure out what class of problems is it. $\endgroup$
    – NicoCaldo
    Mar 30 '17 at 14:56
  • 1
    $\begingroup$ It is a conditional probability / Bayesian question $\endgroup$
    – Henry
    Mar 30 '17 at 14:58
  • $\begingroup$ So, I consider the events $E=$"launch of the first coin" and $F=$"head on the 4th launch". I need to find $P(E|F)=\frac{P(F|E)P(E)}{P(F|E)P(E)+P(F|E^C)P(E^C)}$ with $P(F|E)=\frac{4}{5}^3*\frac{1}{5}$, $P(F|E^C)=\frac{6}{7}^3*\frac{1}{7}$ and $P(E)=P(E^C)=0.5$. And at this I resolve the equation, right? $\endgroup$
    – NicoCaldo
    Mar 31 '17 at 9:58
  • 1
    $\begingroup$ Yes. You get the same result with $P(E\mid F)=\frac{P(E \cap F)}{P(F)}=\frac{P(E \cap F)}{P(E\cap F)+P(E^C\cap F)}$ $\endgroup$
    – Henry
    Mar 31 '17 at 11:06
0
$\begingroup$

Consider the events

  • $E=$"launch of the first coin"
  • $F=$"head on the 4th launch"

I need to find $$P(E|F)=\frac{P(F|E)P(E)}{P(F|E)P(E)+P(F|E^C)P(E^C)}$$ with $$P(F|E)=(\frac{4}{5})^3∗\frac{1}{5}$$ and $$P(F|E^C)=(\frac{6}{7})^3∗\frac{1}{7}$$ I know $$P(E)=P(E^C)=0.5$$ So now I can replace with the number and find the answer

$\endgroup$
1
  • 1
    $\begingroup$ Quite right. You might notice that since $P(E)$ and $P(E^C)$ are equal, your first formula simplifies to $$P(E|F)={P(F|E)\over P(F|E)+P(F|E^C)}$$ There's no getting around the rest of the arithmetic, though. $\endgroup$ Mar 31 '17 at 13:36

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.